2008
DOI: 10.1002/ccd.21583
|View full text |Cite
|
Sign up to set email alerts
|

Concordant improvements in coronary flow reserve and ST‐segment resolution during percutaneous coronary intervention for acute myocardial infarction: A benefit of postconditioning

Abstract: Ischemic postconditioning, as described, can be expeditiously performed during PCI for STEMI. Concordant changes in coronary flow reserve and ST segment resolution, measures of microcirculatory function, and myocardial perfusion, were greater in postconditioned patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 39 publications
(49 reference statements)
3
71
1
4
Order By: Relevance
“…Several small human trials reported that ischemic postconditioning with primary PCI significantly reduced enzymatic infarct size compared with conventional primary PCI in patients with ST-segment-elevation myocardial infarction (STEMI). [5][6][7] However, the results of studies using magnetic resonance imaging to evaluate the effects of postconditioning on infarct size were inconsistent. [8][9][10][11][12] Moreover, most studies have not reflected current practice patterns such as thrombus aspiration, predilation before stenting, or use of glycoprotein IIb/IIIa inhibitors.…”
Section: October 22 2013mentioning
confidence: 99%
“…Several small human trials reported that ischemic postconditioning with primary PCI significantly reduced enzymatic infarct size compared with conventional primary PCI in patients with ST-segment-elevation myocardial infarction (STEMI). [5][6][7] However, the results of studies using magnetic resonance imaging to evaluate the effects of postconditioning on infarct size were inconsistent. [8][9][10][11][12] Moreover, most studies have not reflected current practice patterns such as thrombus aspiration, predilation before stenting, or use of glycoprotein IIb/IIIa inhibitors.…”
Section: October 22 2013mentioning
confidence: 99%
“…In AMI, the application of Postcon stimuli 6 -12 h after presenting with chest pain can reduce surrogate markers of infarction by 27% (237), 36% (143), or as much as 40 -50% (216). Other small trials detect improvements in functional outcomes without alterations in markers of cell death (125).…”
Section: Clinical Application Of Precon and Postconmentioning
confidence: 99%
“…Laskey и соавт. [49] опубликовали ре-зультаты своих наблюдений за больными (n =24) ОИМ с подъемом сегмента ST. Всем им проводили коронарную ангиопластику в течение 6 ч от момента возникновения коронароокклюзии. Среднее время от момента коронаро-тромбоза до реперфузии составило 4 ч. Посткондициони-рование воспроизводили с помощью 2 циклов дефляции (3 мин) и инфляции (90 с) интракоронарного баллона.…”
Section: данные клинических наблюденийunclassified
“…Больные были разделены на 2 группы: 1) контроль (только ангиопластика; n =12); 2) посткондиционирование (ангио-пластика + посткондиционирование; n =12). Оказалось, что у адаптированных пациентов отмечается более вы-раженное и быстрое разрешение сегмента ST (p =0,0002) [49]. У посткондиционированных больных было отмече-но увеличение коронарного резерва (p<0,0001) по сравне-нию с группой контроля.…”
Section: данные клинических наблюденийunclassified
See 1 more Smart Citation